PENGARUH BALIHO TERHADAP PILIHAN POLITIK MASYARAKAT KELAS MENENGAH PADA PILKADA DI KOTA MAKASSAR - Andu, Christine Purnamasari; Hardiyanti, Sartika Dwi (Universitas 17 Agustus 1945 Surabaya, 2019)
The research aims to know and analyze (1) the effect of using ‘baliho’ towards political choice of middle class society in Makassar City, (2) the importance of using ‘baliho’ as promotional media for regional head candidates to middle class society in Makassar City, and (3) the response of middle class society towards use of ‘baliho’. This research use qualitative descriptive methods. There were 12 (twelve) informants as samples were interviewed and the results of these interviews were analyzed using several theories. The research result indicate that (1) political choice of middle class society not depends on ‘baliho’ because research result indicated that 50% of informants said that their political choice effected by track records, capabilities, and achievements of the candidates not just based on ‘baliho’, (2) according to interviewed with middle class informants indicated that 41.66% informants suggest that candidates are better to directly socialize to society meet them and interact to build two ways communications so both side can get to know each other, and 33.33% suggest candidates are better to use social media and television to promote themselves, (3) response of middle class society about the use of ‘baliho’ showed 83.33% said that ‘baliho’ was just annoying, dirty, untidy, spoil the view of the city, and will produce more waste.Keywords: Baliho, Middle Class, Regional Head Election